LO27: Risk factors for misuse of prescribed opioids: a systematic review and meta-analysis. (May 2019) - Cragg, A.; Kitchen, S.; Hau, J.; Woo, S.; Liu, C.; Doyle-Waters, M.; Hohl, C.
Abstract : Introduction : Increasing opioid prescribing has been linked to an epidemic of opioid misuse. Our objective was to synthesize available evidence about patient-, prescriber-, medication-, and system-level risk factors for developing opioid misuse from prescribed opioids among patients presenting with pain unrelated to cancer. Our hypothesis was that we would identify risk factors predisposing patients to developing opioid misuse.Methods : We developed a systematic search strategy and applied it to nine electronic reference databases and six clinical trial registries. We hand searched related journals and conference proceedings, the reference lists of included studies, and the top 100 hits on Google. We included studies where a medical professional exposed adults or children to an opioid through a prescription. We excluded studies with over 50% cancer patients, palliative patients, and those with illicit opioid initiation. Two reviewers independently reviewed titles, abstracts, and full texts, and extracted data using standardized forms. We assessed study quality using risk of bias. We synthesized effect sizes of dichotomous risk factors on opioid misuse using inverse variance random-effects meta-analysis, and the inverse variance-weighted mean difference between opioid misusers and non-misusers for continuously measured factors. We conducted an a priori defined subgroup analysis among opioid-naïve patients.Results : Among 9, 629 studies, 67 met our inclusion criteria. Among those who had been prescribed outpatient opioids, the following factors were associated with the development of misuse: a prior history of illicit drug use (OR: 4.21, 95% CI: 2.31-7.65), recent benzodiazepine use (OR: 2.57, 95% CI: 1.23-5.38), any mental health diagnosis (OR: 2.45, 95% CI: 1.91-3.15), any short acting (IR) opioid prescription (OR: 2.40, 95% CI: 1.15-5.02), younger age (OR: 2.19, 95%CI: 1.81-2.64), and male sex (OR: 1.23, 95% CI: 1.10-1.36). Among studies limiting their population to opioid-naïve patients, younger age was the most significant risk factor for opioid misuse (OR: 5.42, 95% CI:1.51-19.43).Conclusion : Of the risk factors examined, non-cancer pain patients with a prior history of substance use or mental health diagnoses were at highest risk for prescription opioid misuse. Younger opioid-naïve patients were at highest risk of misuse. Clinicians should consider these risk factors when managing acute pain in the emergency department.